Aqueous Zinc–Tellurium Batteries with Ultraflat Discharge Plateau and High Volumetric Capacity. Issue 42 (13th September 2020) - Chen, Ze; Yang, Qi; Mo, Funian; Li, Na; Liang, Guojing; Li, Xinliang; Huang, Zhaodong; Wang, Donghong; Huang, Weichun; Fan, Jun; Zhi, Chunyi
Abstract: Traditional aqueous zinc‐ion batteries (ZIBs) based on ion‐intercalation or surface redox behaviors at the cathode side suffer severely from an unsatisfactory specific capacity and unstable output potential. Herein, these issues are applied to a conversion‐type zinc–tellurium (Zn–Te) battery. Typically, this battery works based on a two‐step solid‐to‐solid conversion with the successive formation of zinc ditelluride (ZnTe2 ) and zinc telluride (ZnTe). It delivers an ultrahigh volumetric capacity of 2619 mAh cm −3 (419 mAh g −1 ), 74.1% of which is from the first conversion (Te to ZnTe2 ) with an ultraflat discharge plateau. Though reported first in a challenging aqueous environment, this Zn–Te battery demonstrates an excellent capacity retention of >82.8% after 500 cycles, which results from the elimination of the notorious "shuttle effect" due to the solid‐to‐solid conversion behaviors. In addition, a quasi‐solid‐state Zn–Te battery is also fabricated, exhibiting superior flexibility, robustness, and good electrochemical performance. This work develops a novel cathode material based on conversion‐type ion‐storage mechanism. The system is attractive due to its ultrastable energy output, which is rarely reported for ZIBs. Abstract : A new conversion‐type zinc‐ion battery is developed, in which the chalcogen element tellurium serves as the cathode in aqueous electrolytes. Based on the two‐step solid‐to‐solid conversion mechanism with the successive formation of zinc ditelluride and zinc telluride, this battery avoids the shuttle effect and exhibits an ultraflat discharge plateau, high volumetric capacity, as well as long cycling life.